PELAKSANAAN PEMBELAJARAN BERBASIS BAHASA IBU DI SEKOLAH DASAR - Lusia Florida Dhiu; Dimas Qondias; Pelipus Wungo Kaka; Ermelinda Yosefa Awe (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to determine the imlementation of mother tongue-based learning conducted at Citra Bakti Elementary School, Golewa District, Ngada Regency. This study used a qualitative approach, data were collected through intervoews, observation, and documentation. Once the data were gathered, the analysis was conducted by reducing and presenting it as well as drawinh conclusion from the findings. This study resulted in finding out that mother tongue based instruction had not been designed yet. These findings also indicated the needs to comduct early recession to reveal groups of students who had the same mother tongue basis. it is also necessary to state that designing an instruction by adjusting to students needs and characteristics with mother tongue basis is imminent to be carried out.